2022
DOI: 10.3389/fmicb.2022.860288
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of Carbapenemases in Enterobacterales With a New Rapid and Simplified Carbapenemase Detection Method Called rsCDM

Abstract: ObjectiveThis study aimed to develop a new rapid and simplified carbapenemase detection method (rsCDM) for detection and characterization of carbapenemase with 3-aminophenylboronic acid (APBA), ethylenediaminetetraacetic acid (EDTA), and cloxacillin (CLO) β-lactamase inhibitors.MethodsA panel of 182 carbapenem-resistant Enterobacterales (CRE) strains with blaKPC (88), blaNDM (60), blaIMP (10), blaVIM (3), blaOXA-181 (5), blaKPC, and blaNDM (7), porin changes in combination with an extended-spectrum β-lactamase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
0
1
Order By: Relevance
“…The bla TEM gene (n = 29) was the most commonly detected among the β-lactamase-encoding genes, followed by bla SHV (n = 4), bla KPC (n = 2), and bla CTX−M (n = 2). KPC is a multienzyme belonging to class A carbapenemases, which are usually produced by Enterobacteriaceae, particularly K. pneumoniae and P. aeruginosa (Poirel et al, 2010;Liao et al, 2022). In the present study, K. pneumoniae, H. influenzae, and P. mirabilis were identified in the specimens with the bla KPC gene detected by TNPseq; however, the conventional culture showed no evidence of microbial growth.…”
Section: Discussioncontrasting
confidence: 49%
“…The bla TEM gene (n = 29) was the most commonly detected among the β-lactamase-encoding genes, followed by bla SHV (n = 4), bla KPC (n = 2), and bla CTX−M (n = 2). KPC is a multienzyme belonging to class A carbapenemases, which are usually produced by Enterobacteriaceae, particularly K. pneumoniae and P. aeruginosa (Poirel et al, 2010;Liao et al, 2022). In the present study, K. pneumoniae, H. influenzae, and P. mirabilis were identified in the specimens with the bla KPC gene detected by TNPseq; however, the conventional culture showed no evidence of microbial growth.…”
Section: Discussioncontrasting
confidence: 49%
“…Nordmann et al 16 had reported this test to be 100% sensitive for detection of carbapenemase production but subsequent studies revealed a lower sensitivity of <90%. [17][18][19] Limitations of Carba NP test is that it cannot differentiate between different classes of carbapenemases, low sensitivity for detection 22,[24][25][26][27][28] It is preferable for resource limited laboratories as it is easy to do and inexpensive test. As eCIM is also performed along with mCIM for the detection of MBL's it will be helpful for differentiation between serine & metallo beta-lactamases.…”
Section: Discussionmentioning
confidence: 99%